Stress-reducing interventions in pregnancy for the prevention of preterm birth: a systematic review and meta-analysis - Laura E. Janssen; Adelia A. Gieskes; Marjolein Kok; Christianne J. M. de Groot; Martijn A. Oudijk; Marjon A. de Boer (Taylor & Francis Group, 2023)
AbstractPreterm birth (PTB) is the leading cause of neonatal morbidity and mortality. Maternal stress during pregnancy is an established risk factor for PTB. We aimed to review the effects of stress-reducing interventions during pregnancy on PTB. Studies reporting on stress-reducing interventions during pregnancy and PTB rates in general low-risk obstetric populations were included. PTB rates, low birth weight (LBW) rates, mean gestational age and birth weight, maternal anxiety and stress, and adverse perinatal outcomes were investigated. Data were extracted using a standardized extraction form, pooled effect sizes were calculated with the random effects model. Ten studies with a total of 4.816 women were included. The interventions included Pilates, yoga, a multidisciplinary stress reduction program, combination therapy (combining mindfulness, yoga, music, baby bonding, and education), and hypnosis. The incidence of PTB was significantly lower in the intervention group (RR 0.50, 95% CI 0.35 − 0.71). The overall quality of the included studies was low, and the risk of bias was high. In conclusion, this study provides evidence supporting the potential efficacy of stress-reducing interventions in reducing the incidence of PTB in low-risk women. We propose a RCT of high quality to determine the effectiveness of stress-reducing interventions in reducing PTB risk.